Pemetaan Risiko dan Strategi Mitigasi pada Usahatani Padi dengan Pendekatan House of Risk - Lia Julianti; Adi Suyatno; Imelda Imelda (Universitas Galuh, 2026)
Rice is a staple food crop that plays an important role in fulfilling the food consumption of the Indonesian people. Farmers in rice farming face various uncertainties that could potentially reduce production and income. The presence of various risks in rice farming, such as production, price, financial, institutional, and human risks, can be obstacles to achieving optimal production and income. This study aims to analyze the occurrence of risks and sources of risks as well as to analyze the priority of risk mitigation strategies for rice farming in Sungai Itik Village, Sungai Kakap District, Kubu Raya Regency. This research employs a descriptive quantitative method with the house of risk analysis tool. The sampling technique used in this study is simple random sampling of 88 rice farmers in Sungai Itik Village. The research results show that in HOR phase 1, there are 10 risk events and 19 risk sources. The 7 priority risk sources for rice farming in Sungai Itik Village are excessive rainfall, rodent pest attacks, decreased farmer solidarity, attacks by weaver birds, attacks by sparrows, high household expenditure compared to farming, and a decline in rice farming income during the previous planting season. In HOR phase 2, there are 7 mitigation strategies to address these priority risk sources: simultaneous rice planting, pesticide use, scarecrow use, crop diversification, rodent poison use, conducting rat hunts, and strengthening the role of farmer groups.